2012
DOI: 10.1109/tns.2012.2183385
|View full text |Cite
|
Sign up to set email alerts
|

Reflectivity Spectra for Commonly Used Reflectors

Abstract: Abstract-Monte Carlo simulations play an important role in developing and evaluating the performance of radiation detection systems. To accurately model a reflector in an optical Monte Carlo simulation, the reflector's spectral response has to be known. We have measured the reflection coefficient for many commonly used reflectors for wavelengths from 250 nm to 800 nm. The reflectors were also screened for fluorescence and angular distribution changes with wavelength. The reflectors examined in this work includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 24 publications
4
90
0
Order By: Relevance
“…After some experimentation [22,23], Lumirror 188 E6SR was chosen. Lumirror is a highly reflective voidbased reflector between two protective layers [24,25]. These protective layers allow the reflector to be submerged in scintillator without significant loss of reflectivity [22].…”
Section: Lumirror Reflectormentioning
confidence: 99%
See 1 more Smart Citation
“…After some experimentation [22,23], Lumirror 188 E6SR was chosen. Lumirror is a highly reflective voidbased reflector between two protective layers [24,25]. These protective layers allow the reflector to be submerged in scintillator without significant loss of reflectivity [22].…”
Section: Lumirror Reflectormentioning
confidence: 99%
“…It is built from carbon steel and internally protected from corrosion by a layer of Permatex resin. In order to improve the light collection efficiency, the interior surface of the WCV and the exterior of the LSV sphere are covered with a layer of Tyvek [24,41].…”
Section: The Water Cherenkov Vetomentioning
confidence: 99%
“…In the further studies we used OKEN-6262A. It was already demonstrated that the Gore-Tex teflon has the largest reflectivity among the well-known soft reflectors even in the ultraviolet (UV) range [8]. We measured signals from the counters with the teflon of different thicknesses.…”
Section: Improvement Of the Light Outputmentioning
confidence: 99%
“…This prototype has an excellent resolution (FWHM 5.9% @ 662 keV) for a big CsI(Tl) crystal based detectors. This is a result of ESR film reflector usage (Janecek, 2012).…”
Section: Investigation Tests Of the Gris Detector Prototypesmentioning
confidence: 99%